Answer:
88 inches
Step-by-step explanation:
formula for circumference: 2pir or pi*diameter
22/7*28=88
88 inches
<h3>
Answer: Point E is located at (2, 3)</h3>
====================================
Explanation:
The sequence PQRST has T as the last letter.
The sequence ABCDE has E as the last letter
The two letters T and E pair up or they correspond. So T will rotate to land on point E. Or T will rotate to point E's location.
Point T is at location (-3,2). So x = -3 and y = 2.
-------
Use the rule
(x,y) ---> (y, -x)
which is the rule we use when we rotate any point 90 degrees clockwise around the origin. We swap the x and y coordinates, then change the sign of the second coordinate (after the swap happens).
This means,
(-3, 2) ----> (2, -(-3)) = (2, 3)
or simply
(-3, 2) ---> (2, 3)
.33 in its simplest form is 1/3 I think
Answer:
the mean of it all will increase
Step-by-step explanation:
Answer:
y
=
2
x
−
1
Explanation:
First, we need to determine the slope of the line. The formula for determining the slope of a line is:
m
=
y
2
−
y
1
x
2
−
x
1
where
m
is the slope and the x and y terms are for the points:
(
x
1
,
y
1
)
and
(
x
2
,
y
2
)
For this problem the slope is:
m
=
3
−
−
1
2
−
0
m
=
3
+
1
2
m
=
4
2
m
=
2
Now, selecting one of the points we can use the point slope formula to find the equation.
The point slope formula is:
y
−
y
1
=
m
(
x
−
x
1
)
Substituting one of our points gives:
y
−
−
1
=
2
(
x
−
0
)
y
+
1
=
2
x
Solving for
y
to put this in standard form gives:
y
+
1
−
1
=
2
x
−
1
y
+
0
=
2
x
−
1
y
=
2
x
−
1
Answer linky
=
2
x
−
1
Explanation:
First, we need to determine the slope of the line. The formula for determining the slope of a line is:
m
=
y
2
−
y
1
x
2
−
x
1
where
m
is the slope and the x and y terms are for the points:
(
x
1
,
y
1
)
and
(
x
2
,
y
2
)
For this problem the slope is:
m
=
3
−
−
1
2
−
0
m
=
3
+
1
2
m
=
4
2
m
=
2
Now, selecting one of the points we can use the point slope formula to find the equation.
The point slope formula is:
y
−
y
1
=
m
(
x
−
x
1
)
Substituting one of our points gives:
y
−
−
1
=
2
(
x
−
0
)
y
+
1
=
2
x
Solving for
y
to put this in standard form gives:
y
+
1
−
1
=
2
x
−
1
y
+
0
=
2
x
−
1
y
=
2
x
−
1
Answer link